High Temperature Exposure Assessment of Graphene Oxide Reinforced Cement - Yan, Jianwei; Wang, Jiankang; Chen, Hengyi; Xiang, Ping (Frontiers in Materials, 2022)
This paper aims to carry out a high temperature exposure assessment for graphene oxide reinforced cement in terms of weight loss, the flexural strength and compressive strength. Different additive amounts of graphene oxide in cement are experimentally studied to unfold its effect on enhancing the mechanical performance of prepared graphene oxide reinforced cement. Temperatures are chosen as the room temperature, 200°C, 400°C, 600°C and 800°C, respectively, corresponding to different reaction status of cement. It is found that as the temperature increases, the water evaporates from the graphene oxide reinforced cement. Evaporated quantity of water relies on the reaction status and the relation between weight loss and temperature is provided. Benefited from the bonding effects of graphene oxide, hydrated calcium silicate hydrate (C-S-H) is chemically produced and thus formed a reticular bridging system which is greatly helpful to enhance the flexural strength. Unlike the flexural strength, adding GO into cement statistically has little effect on the compressive strength except when the temperature rises up to 800°C due to the occurrence of decarburization from dehydration.